Scaling Up Rural Sanitation : Partnering on the Road Towards Achieving Total Sanitation in East Africa - World Bank (Washington, DC, 2014)
In 2000, the United Nations Development Program set a Millennium Development Goal (MDG) to reduce, by half, the number of people without access to basic sanitation by 2015. In 2008, when projections showed that countries in Africa were unlikely to reach this target, delegates from 32 African countries drafted and signed the eThekwini Declaration and AfricaSan action plan to renew commitments and identify strategic actions. At the East Africa Sanitation Conference held March 2010, analysis of progress to date showed that most countries had national sanitation policies and plans, an encouraging sign, but that poor coordination, particularly at district level, continued to hamper improvements and that budget allocations for sanitation remained far below the target of 0.5 percent of Gross National Product (GNP) recommended in the eThekwini declaration.